Seed treatment reagent for direct seeding paddy rice. - Syed Rastan, Syed Omar; Mohd Hanif, Ahmad Husni; Mohd Saud, Halimi (2007)

(untitled)
This is a special formulated seed treatment reagent consists of hydrogen peroxide, sulphuric acid, and formaldehyde to enhance rapid shoot and root germination of paddy seed, for direct seeding rice grown under aerobic and anaerobic systems. Hydrogen peroxide (H2O2) is used in the formulation to provide active oxygen, which is a vital factor in shoot and root germination and growth. The use of this formulation for both the aerobic and anaerobic direct seeding and growth. The use of this formulation for both the aerobic and anaerobic direct seeding vigor that out complete the weed growth and increase the rice viability.